ANALYSIS OF FLEXIBLE WORKING ARRANGEMENT (FWA) POLICY IMPLEMENTATION IN EAST JAVA PROVINCIAL GOVERNMENT RESPONDING TO SECURITY SITUATION: EDWARDS III MODEL PERSPECTIVE - Muttaqin, Zainal; Agustina, Laili Dwi (Journal of Social Politics and Governance (JSPG), 2025)
This study analyzes the implementation of Flexible Working Arrangement (FWA) policy enacted by East Java Provincial Government through Governor's Circular Letter Number 11410 of 2025 in response to security dynamics during September 1-4, 2025. Employing a descriptive qualitative approach with Edwards III Implementation Model as analytical framework, this research examines four key variables: communication, resources, disposition, and bureaucratic structure. The analysis reveals that FWA policy represents an adaptive strategy successfully balancing employee safety protection and essential public service continuity. Implementation success was supported by structured policy communication, utilization of existing digital infrastructure, strong leadership commitment, and bureaucratic structure flexibility in operational decision decentralization. This study recommends institutionalizing FWA mechanism within permanent Business Continuity Plan (BCP) framework and developing output-based performance evaluation system to measure adaptive policy effectiveness during crisis.